2015
DOI: 10.1074/jbc.m114.627455
|View full text |Cite
|
Sign up to set email alerts
|

Human SLC4A11 Is a Novel NH3/H+ Co-transporter

Abstract: Background: Mutations in SLC4A11 result in corneal endothelial dystrophies; however, the transport characteristics of this membrane protein remain unclear. Results: SLC4A11 showed NH 4 Cl-dependent currents indicative of a NH 3 /H ϩ electrogenic co-transport mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
65
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 41 publications
13
65
0
1
Order By: Relevance
“…SLC4A11 contributes to the water ''pump'' as a H þ /OH À transporter and by facilitating a water flux. 2,3 SLC4A11 also transports ammonia, 4,5 which may prevent toxic accumulation of this metabolite. 6 SLC4A11 is the only defective gene found in patients with the rare recessive disease congenital hereditary endothelial dystrophy (CHED), which has onset at birth or early in life.…”
mentioning
confidence: 99%
“…SLC4A11 contributes to the water ''pump'' as a H þ /OH À transporter and by facilitating a water flux. 2,3 SLC4A11 also transports ammonia, 4,5 which may prevent toxic accumulation of this metabolite. 6 SLC4A11 is the only defective gene found in patients with the rare recessive disease congenital hereditary endothelial dystrophy (CHED), which has onset at birth or early in life.…”
mentioning
confidence: 99%
“…In support of a common water and NH 3 permeability pathway, a H ϩ -coupled NH 3 co-transporter (SLC4A11) has been demonstrated to allow for water permeation (33,34).…”
mentioning
confidence: 99%
“…Moreover, recent studies suggest that human SLC4A11 is not involved in HCO 3 − transport but appears to transport H + (OH − ) in a sodium‐independent fashion (Kao et al ; ; Myers et al ) although some authors have reported H + (OH − ) flux is coupled with Na + (Jalimarada et al ; Ogando et al ). Given that the ion transport characteristics of Slc4a11 have not been fully elucidated and remain controversial (Park et al ; Praetorius et al ; Ogando et al ; Kao et al ; Zhang et al ), we evaluated the function of heterologous expressed mouse Slc4a11 and Slc4a7 in CHO‐K1 cells. Figure A shows that CHO‐K1 cells loaded with the pH‐sensitive fluorescent dye BCECF and expressing the mouse Na + ‐HCO 3 − cotransporter Slc4a7, also known as Nbcn1 and NBC3, mediated a Na + ‐dependent intracellular alkalization (HCO 3 − influx) when a large inward‐directed Na + gradient was introduced to the Na + ‐depleted CHO‐K1 cells [white circles; the Slc4a7 ‐transfected cell data are comparable to a previous study (Yang et al )].…”
Section: Resultsmentioning
confidence: 99%
“…SLC4A11 has the least sequence similarity to the other SLC4 HCO 3 − transporter members and its function remains controversial (Parker et al ). Originally thought to be an electrogenic sodium borate cotransporter (Na + (n)‐B(OH − ) 4− ) or cation (Na + or H + ) permeation pathway (Park et al ), subsequent studies reported that SLC4A11 mediates Na + –OH − cotransport (equivalent to a Na + /H + exchanger) (Jalimarada et al ; Ogando et al ); NH 4 + permeation (Ogando et al ), water flux (Vilas et al ; Soumittra et al ), H + (OH − ) transport (Jalimarada et al ; Kao et al , ; Myers et al ), and/or NH 3 –2H + cotransport (Kao et al ; Zhang et al ). Unlike other SLC4 transporters, SLC4A11 does not transport HCO 3 − (Jalimarada et al ; Ogando et al ; Loganathan et al ).…”
Section: Introductionmentioning
confidence: 99%